Assessing the effects of entrepreneurship on Nigeria's economic growth - EKANEM, Emmanuel Uduak (KDI School, 2016)
The aim of this study was to critically assess the effects of entrepreneurship on the economic growth of Nigeria, and how she usurped South Africa to become the largest economy in Africa and the sixth fastest growing economy in the world after Indonesia (Bloomberg 2015). From a theoretical perspective, this study bridges the gap of knowledge on the impact of entrepreneurship on economic growth for Nigeria, contributing to the universal body of knowledge on this subject matter, thereby supporting the nexus between economic growth and entrepreneurship. From a pragmatic stand point, this study illustrates the effects of entrepreneurship on Nigeria’s economic growth, obstacles to entrepreneurship in Nigeria, and how to create an enabling environment, in which inspirations are triggered and for entrepreneurship to thrive in Nigeria. Nigeria is a sovereign state with numerous human and natural resources bequeathed on her by God, but has the promotion and rise of entrepreneurship really helped Nigeria or has it made things worse off for her? This study focused on some of the possible effects of entrepreneurship in Nigeria and obstacles to entrepreneurship in Nigeria. For analysis purposes, this study utilized empirical methods like; multiple regression, chi-square, independent samples test (t-test), ANOVA. The analysis also employed frequency distribution tables, bar charts and pie charts. The findings showed that though Nigerians are predisposed to entrepreneurship regardless of their ethnicity, female entrepreneurs face more obstacles than male entrepreneurs in Nigeria. The study also revealed that though government’s entrepreneurship programs can stimulate economic growth, it cannot fully address the problem of unemployment in Nigeria.
Thesis(Master) --KDI School:Master of Development Policy,2016